1995
DOI: 10.1111/j.1365-2109.1995.tb00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the environmental impacts and consent compliance of freshwater fish farms

Abstract: Strategies for monitoring the chemical and biological impacts of freshwater land-based and cage fish farms in the West of Scotland are described and the results of monitoring are presented. The compliance of landbased farms with discharge consents is discussed. The impact of fish farming on receiving water chemistry was found to be limited, but effects on benthic invertebrate communities in both running waters and lochs were more readily detectable, although generally localized in the immediate vicinity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…These results are supported by previous studies, where bacteria downstream of fish farm outflows showed much higher densities and heterotrophic activity due to the accumulation of generated organic matter (Boaventura et al, 1997;Carr and Goulder, 1990). Moreover, the presence of occasionally large mats of sewage fungus and bacteria downstream of the Molco Aquaculture effluent reinforces that the enhanced DOM concentration downstream of Molco Aquaculture (and the other studied fish farms) also increases the microbial respiration of the receiving stream, as clearly shown by Doughty and McPhail (1995) for similar Scottish aquaculture systems.…”
Section: General Effects and Fate Of Dom From Land-based Aquaculture supporting
confidence: 90%
See 1 more Smart Citation
“…These results are supported by previous studies, where bacteria downstream of fish farm outflows showed much higher densities and heterotrophic activity due to the accumulation of generated organic matter (Boaventura et al, 1997;Carr and Goulder, 1990). Moreover, the presence of occasionally large mats of sewage fungus and bacteria downstream of the Molco Aquaculture effluent reinforces that the enhanced DOM concentration downstream of Molco Aquaculture (and the other studied fish farms) also increases the microbial respiration of the receiving stream, as clearly shown by Doughty and McPhail (1995) for similar Scottish aquaculture systems.…”
Section: General Effects and Fate Of Dom From Land-based Aquaculture supporting
confidence: 90%
“…This may result in a complete shift of species in all large groups when comparing stretches up-and downstream of land-based aquacultures. This biotic effect has been documented by Doughty and McPhail (1995), showing changes in benthic invertebrate communities downstream of aquaculture effluents in fluvial ecosystems.…”
Section: General Effects and Fate Of Dom From Land-based Aquaculture mentioning
confidence: 95%
“…Cold water stream ecosystems can show a typical reaction or shift in the river continuum when disturbed by nutrient‐rich trout farm effluents (Loch, West & Perlmutter 1996). Effluents with high organic loads [biological oxygen demand in 5 days (BOD 5 )>2.1 mg L −1 ] show, in the vicinity of the discharge point (maximum 100 m), a dominance of heterotrophic bacteria and sewage fungi suppressing the primary production (Doughty & MCPhail 1995; Loch et al 1996; Villanueva, Queimalinos, Modenutti & Ayala 2000). The heterotrophic dominance is followed by an increased primary production measured as chlorophyll a .…”
Section: Potential Impact Of Aquaculture Effluents On Adjacent Ecosysmentioning
confidence: 99%
“…The heterothrophic and euthrophic change is often accompanied by a shift in the macroinvertebrate community, from intolerant, oligosaprobic species upstream the discharge point, to nutrient‐tolerant species, indicating an ecosystem degradation (Camargo 1994; Doughty & McPhail 1995; Loch et al 1996; Selong & Helfrich 1998). The macroinvertebrate community needs the longest distance from the point source for recovery.…”
Section: Potential Impact Of Aquaculture Effluents On Adjacent Ecosysmentioning
confidence: 99%
“…Aquaculture effluents can affect downstream macroinvertebrate and fish communities. Intolerant Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa generally decrease, whereas tolerant taxa (Diptera, Gastropoda, Hirudinea, Oligochaeta) increase (Carmago 1992;Doughty and McPhail 1995;Henderson and Ross 1995;Loch et al 1996). Fish biomass may increase with nutrient enrichment because of enhanced primary production and macroinvertebrate biomass (Rasmussen 1986).…”
mentioning
confidence: 99%